UMP STEM Carnival inculcates culture of scientific, creative and innovative thinking - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 5 October 2022 - The organisation of Science, Technology, Engineering and Mathematics (STEM) Carnival attracted more than 1,000 students from schools around Pahang to participate in various programmes based on integrated learning in the field of STEM to enhance competitiveness in the field of science and technology to school students.